2011
DOI: 10.1002/jsfa.4522
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐induced modulation in inorganic nutrients, antioxidant enzymes, proline content and seed oil composition in safflower (Carthamus tinctorius L.)

Abstract: Overall, high salt tolerance of Safflower-39 could be attributed to Na(+) and Cl(-) exclusion, high accumulation of K(+) and free proline, enhanced CAT activity, seed oil α-tocopherols and palmitic acid contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…Safflower seed and oil yield were not affected with increase in electrical conductivity of soil, but the oil content and 1000-seed weight were increased slightly with increase in soil salinity (Bassil and Kaffka 2002). Siddiqi et al (2011) found a decrease in seed yield, number of seed per capitula, and 1000-seed weight while α-tocopherols, stearic, oleic, and linoleic acid contents were not affected. The application of 50 mM NaCl decreased the total lipid contents in both roots and aerial parts with great variations in the fatty acid profile.…”
Section: Seed Oil Yield and Qualitymentioning
confidence: 79%
See 3 more Smart Citations
“…Safflower seed and oil yield were not affected with increase in electrical conductivity of soil, but the oil content and 1000-seed weight were increased slightly with increase in soil salinity (Bassil and Kaffka 2002). Siddiqi et al (2011) found a decrease in seed yield, number of seed per capitula, and 1000-seed weight while α-tocopherols, stearic, oleic, and linoleic acid contents were not affected. The application of 50 mM NaCl decreased the total lipid contents in both roots and aerial parts with great variations in the fatty acid profile.…”
Section: Seed Oil Yield and Qualitymentioning
confidence: 79%
“…These imbalances may result from the effect of salinity on nutrient availability, competitive uptake, transport, and/or partitioning within the plant caused by physiological inactivation of a given nutrient resulting in increased plant's internal requirement for that essential element (Marschner 1995). In salt-affected soils, excessive buildup of Na + and Cl − ions in the rhizosphere leads to severe nutritional imbalance in safflower due to strong interference of these ions with other essential mineral elements such as potassium (K), calcium (Ca), nitrogen (N), phosphorus (P), magnesium (Mg), iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn) (Hu and Schmidhalter 1998;Siddiqi et al 2011). Na + is the principal toxic ion, which interferes with potassium uptake and transport in safflower leading to disturbance in stomatal modulations and causing water loss and necrosis (Siddiqi et al 2011).…”
Section: Imbalances In Mineral Uptake and Assimilationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that increasing the NaCl concentration significantly reduced the activity of GR and APX activities in all sunflower cultivars except for SOD activity compared to control (Table 6). Glutathione reductase (GR) is a potential enzyme of the ASH-GSH cycle and plays an essential role in the defense system against ROS by sustaining the reduced status of GSH (Gill and Tuteja, 2010 (Siddiqi et al, 2011;Çulha Erdal and Çakirlar, 2014) and sunflower (Rios-Gonzales et al, 2002;Jabeen Accepted paper and Ahmad, 2012). According to our results, SOD seems to be more sensitive in the antioxidative process of salt stressed sunflower plants and more active in cv.…”
Section: Resultsmentioning
confidence: 99%